How Can We Mitigate Coastal Hazards? Tarakan Island Case Study - Pratiwi, Sulistya Rini; Gravitiani, Evi; Nainggolan, Yohanna Thresia; Rahmawati, Meylin (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
Intensity of coastal hazards driven by changes in climate and land use have been increasing in many parts of Indonesia, including Tarakan City, where 36% of the population lives near the coast. The purpose of this study is to determine the value of the WTP and identify the factors that affect the WTP of coastal communities in an effort to overcome the impact of beach abrasion in Tarakan City. The analytical methods used in calculating people's willingness to pay in an effort to overcome the impact of beach abrasion are the Willingness to Pay (WTP) method and multiple linear regression. The results of this study are known to mean that the public's willingness to pay is IDR 61,075. Based on the results of multiple regression analysis, the income variable has a significant effect on the WTP of coastal communities, namely income, age, and education variables, while the number of family members has no significant effect. Also, the coefficient of determination (R2) is 0.2718, or 27.18%, where this value indicates that the variables of income, age, education, and number of family members are able to explain the WTP of coastal communities of 27.18%. While the remaining 72.82% is explained by other variables not included in the regression model. Our findings highlight the value of the community’s willingness to repair coastal hazards through the several scenarios offered. The results indicate an overview of local participation in preserving coastal areas.